(untitled) (Eurasian Journal of Ecology, 2023)
Assessment of genotoxicity of pesticides and biomonitoring of their impact on the population living in the area of ​​disposal of endangered stocks of pesticides are of exceptional importance for regulating the ecological state of the environment and protecting the population. The purpose of this study was to assess the level of cytogenetic damage (chromosomal aberrations) in residents of the villages of Karakastek and Umbetala, Zhambul district, Almaty region, located in areas contaminated with pesticides banned for occurrence more than 10 years ago. The soils of the settlements are contaminated with organochlorine pesticides such as aldrin, deldrin, eldrin, chlorobenzilate and DDT. In food, their content does not exceed the MPC. However, there was an excess of MPC for heavy metals - Ni and Co. The residents of v. Karakastek and Umbetali showed a significant excess of the total frequency of chromosomal aberrations compared to the control (p≤0.01). The occurrence of cases of shift of mutations from the chromatid adrenal glands in the foci of inflammation, the destruction of the nature of chemical mutagenesis. An analysis of the state and dynamics of the level of chromosomal aberrations in the population living in territories contaminated with pesticides can help in developing a rationale for predicting long-term biomedical events and normal control over the health of the population. Key words: pesticides, persistent organic pollutants (POPs), chromosome aberrations (CA), chemical mutagenesis, genotoxicity